2010
DOI: 10.1590/s0100-72032010000600005
|View full text |Cite
|
Sign up to set email alerts
|

Marcadores séricos de estresse oxidativo em mulheres inférteis com endometriose

Abstract: ResumoOBJETIVO: comparar marcadores séricos de estresse oxidativo entre pacientes inférteis com e sem endometriose e avaliar a associação destes marcadores com o estadiamento da doença. MÉTODOS: estudo prospectivo envolvendo a inclusão consecutiva de 112 pacientes inférteis, não-obesas, com idade inferior a 39 anos, divididas em dois grupos: Endometriose (n=48, sendo 26 com endometriose mínima e leve -Estádio I/II e 22 com endometriose moderada e grave -Estádio III/IV) e Controle (n=64, com fator tubário e/ou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 0 publications
0
16
0
10
Order By: Relevance
“…Lesions then continue to infiltrate, develop a blood supply, and synthesize and secrete hormones (exact hormonal milieu depends on each lesion’s secretory profile) (Takeda et al 2004). Systemic and local inflammation and oxidative stress (Andrade et al 2010; Maybin et al 2011) and hormonal alterations (including altered response to hormones and increased lesion hormone synthesis) are proposed mechanisms for endometriosis disease progression (Burney et al 2007; Pan et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Lesions then continue to infiltrate, develop a blood supply, and synthesize and secrete hormones (exact hormonal milieu depends on each lesion’s secretory profile) (Takeda et al 2004). Systemic and local inflammation and oxidative stress (Andrade et al 2010; Maybin et al 2011) and hormonal alterations (including altered response to hormones and increased lesion hormone synthesis) are proposed mechanisms for endometriosis disease progression (Burney et al 2007; Pan et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence that oxidative stress may play a role in endometriosis [4-9], there are other theories that may explain the pathophysiology of this disease. The implantation theory proposes that the retrograde menstruation may result in implantation and growth of endometrial cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have also suggested the possibility of endometriosis is a disease caused or associated with oxidative stress [36-40]. In the presence of pelvic endometriosis, there was activation of macrophages in the peritoneal cavity, which could promote increased production of reactive oxygen species and nitrogen and, consequently, oxidative stress, resulting in lipid peroxidation, its degradation products and the products formed by its interaction with low-density lipoproteins and other proteins [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations